N2+-Lasing Induced by Filamentation in Air for Femtosecond Coherent Anti-Stokes Raman Spectroscopy - Zhao, Xiaodong; Nolte, Stefan; Ackermann, Roland (Conference Proceedings - Lasers and Electro-Optics Society Annual Meeting-LEOS, 2020)
We investigated both ultrashort pulse filamentation and lasing action of N2+ for pump-probe experiments. The CARS signals of air and CO2 were detected with the lasing pulse of N2+ as a probe.
CRIS-Team Scopus Importer:2023-04-20